Non-Self-Averaging in Macroeconomic Models: A Criticism of Modern Micro-founded Macroeconomics - Masanao Aoki; Hiroshi Yoshikawa (Kiel Institute for the World Economy (IfW), 2007)
Using a simple stochastic growth model, this paper demonstrates that the coefficient of variation of aggregate output or GDP does not necessarily go to zero even if the number of sectors or economic agents goes to infinity. This phenomenon known as non-self-averaging implies that even if the number of economic agents is large, dispersion can remain significant, and, therefore, that we can not legitimately focus on the means of aggregate variables. It, in turn, means that the standard microeconomic foundations based on the representative agent has little value for they are expected to provide us with accurate dynamics of the means of aggregate variables. The paper also shows that non-self-averaging emerges in some representative urn models. It suggests that non-self-averaging is not pathological but quite generic. Thus, contrary to the main stream view, micro-founded macroeconomics such as a dynamic general equilibrium model does not provide solid micro foundations.
Keywords: 330; Micro foundations; Macroeconomics; Non-self averaging phenomena; Power laws